Urban Citizenship: A Case Study of Philanthropy by Missionaries in Magelang Municipality - Yudianto Yudianto (Universitas Gadjah Mada, 2017)
This study will answer the question of how far the case of philanthropy action by zending in the Magelang City can be understood as citizenship in the context of the early 20th century? By looking at the relationships between philanthropists and institutional of city council (gemeenteraad) it is expected to clarify their position and function in the early 20th century of colonial cities. In addition to indicating the strengthening of civil society, the case is part of the urban community’s efforts to contribute various forms of participation that are not merely interested in politics or the movement of the nation.